Restitution of Confiscated Property in an Imperial Edict from the Early 4th Century - Robin Repnow (Journal on European History of Law, 2023)
A imperial constitution from the early 4th century (CIL III, 12044 = CIL III, 13569 = ICret I, 18, 189), preserved through an inscription on Crete, contains detailed rules about the return of confiscated goods to their former owners. Since the text, sometimes referred to in the literature as the edictum de bonis restituendis or as the Second Caesariani Decree, is very fragmentarily preserved, its content is difficult to understand. Nonetheless, it represents an important source for both Roman fiscal law and the legislative technique employed by emperors at the beginning of Late Antiquity. The constitution may be dated to the period shortly after Emperor Galerius' accession to power (305/306). However, the often-presumed connection in the literature to other inscriptions of imperial constitutions from the same period, such as the edictum de accusationibus, is less close than sometimes assumed.